2012
DOI: 10.1039/c2em30258f
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and removal of endocrine-disrupting chemicals in wastewater treatment plants in the Three Gorges Reservoir area, Chongqing, China

Abstract: Concentrations of six endocrine-disrupting compounds (EDCs), bisphenol A (BPA), estrone (E(1)), 17β-estradiol (E(2)), estriol (E(3)), 17α-ethynylestradiol (EE(2)) and diethylstilbestrol (DES), were assessed in influents, effluents and excess sludge in ten municipal wastewater treatment plants (WWTPs) in the Three Gorges Reservoir (TGR) area, Chongqing, China. Three types of activated sludge treatment processes, oxidation ditch (OD), reversed anaerobic-anoxic-oxic (rA(2)/O) technology and sequential batch react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 44 publications
1
23
0
2
Order By: Relevance
“…There were no obvious geographical trends. The results coincidentally agreed with other published levels of E2 at several ng g À1 dw in sludge in China (Liu et al, 2011;Ye et al, 2012), but were about 5-20 times lower than the estrogenic activities reported for the sediments of the Haihe and Dagu Rivers, China (Song et al, 2006). The BPs accounted for 0.05-1.47% (mean 0.43%) of the EEQs in sewage sludge samples, indicating minor contributions to the total estrogenic activities.…”
Section: Resultssupporting
confidence: 82%
“…There were no obvious geographical trends. The results coincidentally agreed with other published levels of E2 at several ng g À1 dw in sludge in China (Liu et al, 2011;Ye et al, 2012), but were about 5-20 times lower than the estrogenic activities reported for the sediments of the Haihe and Dagu Rivers, China (Song et al, 2006). The BPs accounted for 0.05-1.47% (mean 0.43%) of the EEQs in sewage sludge samples, indicating minor contributions to the total estrogenic activities.…”
Section: Resultssupporting
confidence: 82%
“…However, if a variety of ligands exist simultaneously, the behavior between them and ERs may change due to their different concentrations and receptor binding abilities, both of which are critical influences on the final effects. The nine selected substances have frequently been found, by chemical analysis, at relatively high concentrations in the aquatic system of China, and all of them have been associated with endocrine disrupting effects (Gong et al, 2012;Lei et al, 2009;Liu et al, 2012;Lu et al, 2010;Sun et al, 2008;Wang et al, 2012;Yan et al, 2012;Ye et al, 2012). Thus, we chose them as representative estrogen-like chemicals that are present in the water environment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were selected in the Web of Knowledge using "China", "effluent * OR wastewater * OR reclaimed water *" and "occurrence * OR determination * OR detection *"as the topics. Studies which failed to provide specific values were not taken into account and 27 documents (Cao et al, 2005;Kloepfer et al, 2005;Peng et al, 2006;Chang et al, 2007;Zeng et al, 2007;Xiao et al, 2008;Li et al, 2009;Duong et al, 2010;Huang et al, 2010;Lv et al, 2010;Ma and Shih, 2010;Zhao et al, 2010a,b;Zhou et al, 2010;Chang et al, 2011;Chen et al, 2011;Li and Zhang, 2011;Liu et al, 2011;Sui et al, 2011;Sun et al, 2011;Tong et al, 2011;Yang et al, 2011;Zhang et al, 2011a,b;Gao et al, 2012;Ye et al, 2012;Zhou et al, 2012;Yuan et al, 2013) were selected for reference. If an OC, such as E1, was reported in several studies, the average concentration was calculated.…”
Section: Occurrencementioning
confidence: 99%